Colon cancer chemoprevention by sage tea drinking: decreased DNA damage and cell proliferation - Pedro, Dalila F. N. (2016)
Salvia officinalis and some of its isolated compounds have been found to be preventive of DNA damage and increased proliferation in vitro in colon cells. In the present study, we used the azoxymethane model to test effects of S. officinalis on colon cancer prevention in vivo. The results showed that sage treatment reduced the number of ACF formed only if administered before azoxymethane injection, demonstrating that sage tea drinking has a chemopreventive effect on colorectal cancer. A decrease in the proliferation marker Ki67 and in H2O2-induced and azoxymethane-induced DNA damage to colonocytes and lymphocytes were found with sage treatment. This confirms in vivo the chemopreventive effects of S. officinalis. Taken together, our results show that sage treatment prevented initiation phases of colon carcinogenesis, an effect due, at least in part, to DNA protection, and reduced proliferation rates of colon epithelial cell that prevent mutations and their fixation through cell replication. These chemopreventive effects of S. officinalis on colon cancer add to the many health benefits attributed to sage and encourage its consumption.